Autoimmunity during lymphopenia a two-hit model - Krupica, Tom Jr (Clinical immunology (Orlando, Fla.), 2006)
The immune system has evolved elaborate mechanisms to respond to diverse antigens while minimizing the risk for autoimmune reactivity. During lymphopenia, however, some mechanisms that normally serve to maintain host tolerance are temporarily suspended. Peripheral T cells proliferate in response to self-antigens in lymphopenic hosts, but proliferation toward these same antigens is prevented when T cell numbers are normal. This process, termed homeostatic peripheral expansion, augments peripheral T cell number and limits repertoire skewing during recovery from lymphopenia and also predisposes lymphopenic hosts to autoimmune disease. This paper reviews murine and human settings in which autoimmunity occurs in the context of lymphopenia. We propose a two-hit model, in which lymphopenia plus another insult is sufficient to induce autoimmune disease. Among the secondary insults that appear sufficient to induce autoimmunity during lymphopenia are overproduction of IL-21 as occurs in the NOD.SCID mouse, depletion of Tregs as demonstrated in murine colitis and gastritis models, and tissue inflammation as seen in HIV infected patients who develop immune reconstitution inflammatory syndrome (IRIS). Delineating critical cofactors which result in autoimmune disease during lymphopenia can provide insight into the pathophysiology of naturally occurring autoimmune diseases as well as generating testable hypothesis for inducing tumor-specific autoimmunity in lymphopenic hosts with cancer